Food intolerance and the food industry - Dean, Taraneh (Woodhead Publishing in food science and technology., 2000)
This book provides food industry professionals with information on food intolerance, including its diagnosis, symptoms, and management. Covers issues such as the handling of allergenic food in retail and manufacturing as well as applicable legislation.